Changes in Antarctic coastline between 1997 and 2016 using RADARSAT and MODIS data. Issue 4 (16th February 2020) - Patel, Shailee; Shah, Esha; Jayaprasad, P.; James, M.E.
ABSTRACT: Studies have already indicated more disintegrations and calving of ice margins and a significant negative ice balance at certain parts of Antarctica in recent times. Changes in extent of ice shelves as well as glacier fronts are indeed good signatures of climate change. This paper essentially discusses the changes in Antarctic ice margins between 1997 and 2016. Change-detection technique has been employed using the Radar Satellite (RADARSAT) mosaic of 1997 and the mosaic of Antarctic ice margins generated using MODerate resolution Imaging Satellite (MODIS) images of 2016, with the help of Earth Resources Development Assessment system (ERDAS) Imagine software. Hotspots, where significant changes occurred, have been identified. Most part of the Antarctic coast between 75° E and 45° W, covering all West Antarctica and about half of East Antarctica, has shown definite retreat during this period. Major retreats are observed over the both sides of Ross ice shelf, Ronne ice shelf, Thwaites glacier, and Mertz glacier. Major advancements are observed over Filchner ice shelf, Amery ice shelf, middle portion of Ross ice shelf, and Stancomwills glacier tongue. Over the East Antarctica, areas of advancement and retreat are nearly same. But, over the West Antarctica, the area of retreat is significantly higher than area of advancement.